2022
DOI: 10.5812/jjm-127842
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Standard Triple Therapy Outcomes in Iranian Population: A Retrospective Population-based Study in Mashhad, Northeast of Iran

Abstract: Background: Helicobacter pylori infection is one of the most prevalent infections in many areas of the world, which is treated with different combinations of medications. Objectives: This study aimed to investigate the response rate and outcomes of H. pylori-infected Iranian patients treated with triple therapy. Methods: The current study examined the records of patients with dyspepsia referred to Imam Reza hospital's gastroenterology clinic in Mashhad, Iran, diagnosed with H. pylori from 2017 to 2019. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Despite several studies have been reported various ranges of NAFLD prevalence in the Iranian general population from 7 to 45%, almost many studies unanimous that this metabolic disorder prevalence is increased approximately 40% in the past two decades [11,12]. This increase with a steep slope can be due to the people's lifestyle changes, as the NAFLD major knew risk factors are obesity, diabetes mellitus, dyslipidemia, and low HDL levels [13]; Moreover, some other conditions and disorders such as viral hepatitis, hypothyroidism, polycystic ovary syndrome, and smoking are under investigations as the possible risk factors of the NAFLD [13][14][15]. A focus on the Iranian adult general population indicated a wide range of the NAFLD prevalence in various regions of the country; however, there is a lack of information about many areas of the country due to a lack of accurate reports [16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite several studies have been reported various ranges of NAFLD prevalence in the Iranian general population from 7 to 45%, almost many studies unanimous that this metabolic disorder prevalence is increased approximately 40% in the past two decades [11,12]. This increase with a steep slope can be due to the people's lifestyle changes, as the NAFLD major knew risk factors are obesity, diabetes mellitus, dyslipidemia, and low HDL levels [13]; Moreover, some other conditions and disorders such as viral hepatitis, hypothyroidism, polycystic ovary syndrome, and smoking are under investigations as the possible risk factors of the NAFLD [13][14][15]. A focus on the Iranian adult general population indicated a wide range of the NAFLD prevalence in various regions of the country; however, there is a lack of information about many areas of the country due to a lack of accurate reports [16].…”
Section: Introductionmentioning
confidence: 99%